Perceptions of Cultural Differences between Turkish and German Societies: Personal Observations of two German Erasmus Students at Karabük University - Neumann, Marie Louise; Knust, Sarah Lena (Journal of History Culture and Art Research, 2014)
Observations of Turkish Culture The above mentioned positive expectations were more than fulfilled. We never thought that people could be so friendly, sociable and warm as the Turkish ones we met here. We are very glad that we have had the chance to make this experience. Our Turkish friends in Karabük try to make our stay as great as possible, they help us to organise our trips and take us to places and sights worth seeing. In addition, they took care for the administrational affairs we had to undergo. For example, on our first day we went through a lot of trouble. However, immediately students on campus asked us if they could help us and do anything for us. When we told them about our problems, they called people who could help us. One of the students actually waited with us for two hours until the professor we had to see had office hours, came with us to meet him in case he was needed as a translator and also drove with us to the police station to get our residence permit. This is something no one in Germany would do for strangers. Germans would have told us where to go and from then on it would have been our problem.